2018
DOI: 10.1007/s13197-018-3093-2
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of flavonoids from 12 species of Korean mulberry leaves

Abstract: The total flavonoids in leaves of 12 varieties of Korean mulberry (Morus alba L.) were determined. Seventeen flavonoids were isolated and analyzed using ultra-performance liquid chromatography coupled with diode array detection and quadrupole time-of-flight mass spectrometry (UPLC–DAD–QTOF/MS). To determine the flavonoid contents, HPLC analysis was performed on these 17 flavonoids. The total flavonoid contents of the 12 varieties of mulberry leaves ranged from 748.5 to 1297.9 mg, with the highest obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 24 publications
(30 reference statements)
4
51
1
Order By: Relevance
“…The main identified polyphenols were chlorogenic acid isomers and glycosides of quercetin and kaempferol, including numerous acetylated and malonylated derivatives ( Table 3). These compounds are the dominant secondary metabolites of mulberry, which was confirmed by literature reports [19][20][21]. However, Yu et al [8], based on HPLC-MS analysis among 19 tested mulberry cultivars, selected only six that exhibited a high polyphenolics content, resulting in a high antioxidant activity of leaf extracts.…”
Section: Resultsmentioning
confidence: 80%
“…The main identified polyphenols were chlorogenic acid isomers and glycosides of quercetin and kaempferol, including numerous acetylated and malonylated derivatives ( Table 3). These compounds are the dominant secondary metabolites of mulberry, which was confirmed by literature reports [19][20][21]. However, Yu et al [8], based on HPLC-MS analysis among 19 tested mulberry cultivars, selected only six that exhibited a high polyphenolics content, resulting in a high antioxidant activity of leaf extracts.…”
Section: Resultsmentioning
confidence: 80%
“…Quercetin-O-glycosides can occur as monosaccharides or oligosaccharides consisting of two or more sugar units. These compounds are widely found in various fruits, vegetables, and other anatomical parts of plants [17][18][19].…”
Section: Flavonolsmentioning
confidence: 99%
“…Another study found that the total flavonoid contents in the fruits, leaves, and roots of two mulberry varieties (M. alba and M. nigra) ranged between 0.8948 and 67.369 mg RE (rutin equivalents)/g of dried extract, with the contents in the leaves and roots being higher than those in the fruit [44]. Recently, Ju et al [37] reported that the total contents of the 17 flavonoids isolated from the leaves of 12 mulberry varieties ranged from 748.5 to 1297.9 mg/100 g DW. In addition, various flavonoid derivatives (moragrols A-D, kaempferol 3-O-rhamnoside-7-O-glucoside, morkotin B, and quercetin 3-O-rhamnoside-7-O-glucoside) other than those found in mulberry fruits in this study were found in mulberry leaves.…”
Section: Flavonoid Contents Of Mulberry Fruitmentioning
confidence: 98%
“…In (Figure 2(c)). Ju et al [37] reported seven new quercetin (morkotin A, B, and C) and kaempferol (moragrol A, B, C, and D) compounds by UPLC-DAD-QTOF/MS analysis of flavonoids from mulberry leaves. However, the quercetin derivatives morkotin A and morkotin C have not previously been reported in mulberry fruit.…”
Section: Isolation and Identification Of Flavonoid Compounds In Mulbementioning
confidence: 99%